Pamphlet by Thomas Johnson, 'Industrial Relations Act, 1946', 28 August 1946, and a newscutting 'Co-operation in Industry', by Johnson, June 1954 , - Johnson, Thomas, 1872-1963 (1946)
Johnson's pamphlet discusses the Labour Court.